ALKBH5-Mediated m6A Modification of A20 Regulates Microglia Polarization in Diabetic Retinopathy - Chen, Tingting; Zhu, Wenhui; Wang, Congyao; Dong, Xia; Yu, Fenfen; Su, Yihua; Huang, Jingwen; Huo, Lijun; Wan, Pengxia (Frontiers in Immunology, 2022)
Background To investigate the role of microglia polarization in the pathogenesis of diabetic retinopathy, and study the mechanism of ALKBH5-mediated m6A modification of A20 of retinal microglia polarization. Methods Diabetics rats were constructed and the M1/M2 polarization of retinal microglia was determined using immunofluorescence, flow cytometry, and quantitative real-time PCR (qRT-PCR). Glucose at different concentrations was added to treat the microglia, and the polarization rate was detected. RNA sequencing was performed to identify the differentially expressed gene in glucose treated microglia, and A20 expression was confirmed by qRT-PCR and western blotting. Lentiviruses encoding shRNA for A20 or overexpressing A20 were constructed to clarify the role of A20 in microglia polarization in vitro and vivo. N6-methyladenosine (m6A) modification level and degradation rate of A20 were determined and m6A related proteins were detected. Results Diabetics rats showed a higher M1 polarization rate but lower M2 polarization rate of retinal microglia. With the increase of glucose concentration, microglia tend to polarize into M1 inflammatory type rather than M2 anti-inflammatory type. Shown by RNA sequencing, glucose treated microglia showed a differentially expressed gene profile, which was enriched in kinds of inflammatory categories and pathways. A20 expression was lower in microglia with glucose treatment, which was demonstrated to negatively regulate the M1 polarization. Moreover, intraocular injection of A20-overexpression lentiviruses (OE-A20) rectified the enhanced M1 retinal microglia polarization of diabetes rats. The higher m6A modification level and faster degradation rate of A20 was observed in glucose treated microglia, which was mediated by m6A demethylase ALKBH5. Conclusion Lower expression A20 resulted in the enhanced M1 polarization of retinal microglia in diabetic retinopathy, which was caused by ALKBH5 mediated m6A modification. This study may provide new perspectives on not only the pathogenesis but also the diagnosis and treatment for diabetic retinopathy.